Model Persamaan Struktural Perilaku Penarikan - Rina Hastuti (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2015)
Every year, goverment lost millions or even billions of rupiahs to compensate the budgets for employee expenditures due to withdrawal behavior. This research used the theory of planned behavior to analyze the antecedents of withdrawal behavior which includes absenteism, lateness, and minor withdrawal such as on the job daydreaming. This research was conducted in Pemerintah Daerah Kabupaten Temanggung, Central Java using 155 employees of 8 local government offices as respondent. The data were collected using questionnaire wich recorded as self report. Data were analyzed using structural equation modelling (SEM) with AMOS 16. Result indicate that perceived behavioral control and family to work conflict were significantly related to withdrawal intentions, which predicted later enactment of withdrawal behavior. Thus, government as the decision maker can decrease withdrawal behavior by primarily focusing on reduce the cause of family work conflict and by implementing organizational practice that make it difficult to commit in withdrawal behavior.